Purchase Decisions Influenced by the Role of Product Innovation and Social Media Through Trust in Coolvita Gummy Health Supplements (A Case Study on TikTok Sales) - Narendra Vishnu Nugraha (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: Competition in the health supplement industry has intensified in the digital era, encouraging brands such as Coolvita Gummy to rely on product innovation and social media marketing. This study aims to analyze the effects of innovation and social media on purchase decisions, with trust examined as a mediating variable. Background Problems: The study addresses the issue of how innovation and social media marketing influence consumer purchase decisions in a highly competitive digital market, and whether trust plays a mediating role in these relationships. Research Methods: A quantitative approach was applied using non-probability sampling with a purposive sampling technique. The respondents consisted of 100 Coolvita Gummy consumers in Indonesia. Data were collected using the PopSurvey by Populix application and analyzed with SmartPLS 3.2.9 through validity, reliability, and outer and inner model testing. Findings/Results: The results indicate that innovation and social media have positive and significant effects on trust. Innovation and trust positively and significantly affect purchase decisions, while social media does not directly affect purchase decisions. Trust significantly mediates the effects of both innovation and social media on purchase decisions. Conclusion: The study concludes that consumer trust is a crucial factor that strengthens the influence of innovation and social media on purchase decisions.